2018
DOI: 10.1007/s10495-018-1466-7
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids of Rosa roxburghii Tratt offers protection against radiation induced apoptosis and inflammation in mouse thymus

Abstract: The present study evaluated the protective effect of the natural compound flavonoids of Rosa roxburghii Tratt (FRT) against γ-radiation-induced apoptosis and inflammation in mouse thymus cells in vivo and in vitro. Thymus cells and mice were exposed to Co γ-ray at a dose of 6 Gy. The radiation treatment induced significant cell apoptosis and inflammation. Radiation increased the expressions of cleaved caspase 3/8-10, AIF, and PARP-1, and FRT could mitigate their activation and inhibit subsequent apoptosis in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Ito et al [4] first reported the isolation and structural characterization of it, which exists in Anoectochilus koshunensis and Anoectochilus formosanus. Researchers have found that kinsenoside had a different multiple pharmacologic activity compared with polysaccharide and flavonoids [5][6][7][8]. As a potential immunosuppressive drug for autoimmune hepatitis, it has a vascular protective effect under high glucose conditions and has been found to enhance the oxidative resistance of diabetic mice [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Ito et al [4] first reported the isolation and structural characterization of it, which exists in Anoectochilus koshunensis and Anoectochilus formosanus. Researchers have found that kinsenoside had a different multiple pharmacologic activity compared with polysaccharide and flavonoids [5][6][7][8]. As a potential immunosuppressive drug for autoimmune hepatitis, it has a vascular protective effect under high glucose conditions and has been found to enhance the oxidative resistance of diabetic mice [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids have been demonstrated to exhibit significant radioprotective capabilities [ 27 ]. Previous studies have shown that FRT reduces apoptosis by regulating caspase 3/8-10, AIF and PARP-1, with inflammatory reactions suppressed through regulation of ICAM-1, IL-1α/IL-6β and TNF-α/NF-КB, thereby enhancing radiation protection [ 28 ]. The aim of this study was to explore the effect of FRT on KO mice including the relationship between PARP-1 and ROS, also ROS and DNA following their exposure to radiation.…”
Section: Introductionmentioning
confidence: 99%
“…It is rich in polyphenols, flavonoids, organic acids, triterpenes, amino acids, polysaccharides and essential oils [23,24,25]. All these elements allow R. roxburghii to deliver a range of health benefits including anti-oxidation, anti-mutagenesis, anti-inflammation, anti-aging and anti-tumor effects [26,27,28,29]. Notably, R. roxburghii has been proved to enhance the expression of anti-oxidative, DNA mismatch repair, and telomere maintenance (i.e., XRCC5) genes in macrophage cells, meaning that R. roxburghii can improve the anti-oxidative capability, reduce the possibility of cancer formation, and prolong the life span in cells [30].…”
Section: Introductionmentioning
confidence: 99%